Adat Bersandi Syarak, Syarak Bersandi Kitabullah: Konstruksi Adat dan Agama dalam Hak Waris Masyarakat Matrilineal - Dara Kartika Rahma (UIN Raden Mas Said Surakarta, 2017)
This study explains how women lose control access to their own inheritance. While the condition of Jambi highland communities is known as a society that adopts the matrilineal kinship system, where women have a strong position in the ownership of inheritance rights and can take decisions in the management of his inheritance. This perception arises from the opinion of some NGOs in Jambi who are running a REDD + program and feel understand the conditions and situation in the Kerinci area. Matrilineal society is considered to facilitate them in socialization related to women empowerment. This research method used ethnography and interview. The results of this study indicate that women are traditionÂ in a subordinated position, religion regulates male authority over women. Religion stands as a custom, while custom can not escape from religion. Religion regulates all the behaviour of villagers in community life. This forms a different knowledge between men and women towards their environment.